Agri Rover Automatic Seedling by Using Amica Board - Subba Rao Peram, Siva Koteswara Rao Chinnam, V. Nagireddy (International Journal of Advanced Science and Technology, 2020)
The revolution in the field of robotics is the combination of number of approaches like mechanical, software technology and electronic control systems. By using advancements in robotics, farming operations and tasks can be performed very effectively, efficiently and in lesser time. Due to raise in demand for agricultural products in terms of quality and quantity and non-availability of labor, Agri rover is the best solution.This model meets the efficient utilization of resources.The plaguing and seed sowing operations are performed by the system using AMICA Board module and iscontrolled by Internet of Things (IoT). The necessity of this small-scale seeding machine is, simple technology driven design and ease of handling. The developed Agri-Rover reducesinvolvement of the human.It improves the speed of seed sowing, seed placement precisions made it usable. Tough and Less cost Agri-Roverfor the small-scale farmers.